ANALYSIS OF THE UNSIGNALIZED INTERSECTION OF MUHARTO ROAD, KI AGENG GRIBIG ROAD, AND MAYJEND SUNGKONO ROAD - M. Sa'dillah; Pamela Dinar Rahma; Claudius Sebi Tawong (Universitas Islam Malang, 2023)
Delays that occur at intersections greatly affect the performance of the road network. The more intersections there are, the greater the delay value will be. One of the intersections in Malang City is the three unsignalized intersections of Muharto Road, Ki ageng Gribig Road, and Mayjend Sungkono Road or also called the Kedungkandang intersection which is the research location. The research aims to determine the performance and project problems at the Kedungkandang Intersection. The data used in the study include road geometric data, traffic volume, acceptance gap, population, and vehicle growth. Based on the 1997 MKJI guide, the results of the study show that the Kedungkandang intersection is included in the level of service criteria C (DS 1.52) with an intersection delay value of 23.29 sec /mp. Based on the processing of gap data with the Raff method, the gap value is 15.1 seconds for the morning, 16.3 seconds for the afternoon, and 17.2 seconds for the afternoon, thus indicating that driver behavior must wait for a gap when entering the main road. The projection results with the placement of right-turn prohibition signs and geometric widening of Muharto Road and Ki Ageng Gribig Road obtained a level of service value of B (DS 0.69) with an Intersection Delay Value of 12.40 sec/smp. Keywords: Gap Acceptance; MKJI 1997; Unsignalized Intersection; Delay.